EXPLORING THE URGENCY OF TEACHING CAMPUS QUALITY FOR STUDENTS OF IKIP MUHAMMADIYAH MAUMERE - Eman Nataliano Busa; Gisela Nuwa (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
The Teaching Campus is a part of the Merdeka Campus program, which presents students from various universities to encourage the teaching and learning process in schools, especially for the elementary school education level, and provide opportunities for students to learn and develop themselves through activities outside the lecture class. IKIP Muhammadiyah Maumere also takes an important role in the teaching campus program by involving the students as pioneers in the teaching campus program. The research purpose of this paper is to find out the urgency of teaching campus quality to IKIP Muhammadiyah Maumere students and the programs participated by students of IKIP Muhammadiyah Maumere in Campus Teaching Activities. The research uses a descriptive qualitative method. The informants of the research involved campus teaching coordinators, field supervisors, and students of the campus teaching at IKIP Muhammadiyah Maumere. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques include data reduction, data display, and data verification. The research results indicate that the urgency of the quality of teaching campus participants is measured by additional skills in the form of certificates of organizational/teaching, academic and non-academic achievements, and parental consent. Campus teaching participants must be able to manage classes and be able to manage time. Campus teaching participants receive financial assistance and recognition for 20 credits of courses that were obtained from the Ministry of Education. Teaching campus participants must be able to make a positive impact by helping the learning activities in schools, assisting school technology, and assisting technology-based school administration. Students participating in teaching campuses must have creativity and innovation that can create a generation of good workers. Campus teaching participants must have a good attitude and behavior. The programs run by Campus Teaching Participants IKIP Muhammadiyah Maumere are the Literacy and Numeracy Learning program, technology adaptation program, and School Administration Assisting program.